Using Digital Social Media Networking Technologies (DSMNT) in an ODL Teachers/Teaching Training and Practice during COVID-19 - Agrawal, Amit; Singh, Abhishek Kumar (JOURNAL OF INDIAN EDUCATION, 2022)
Globally, educational institutions, states and central universities were closed due to the corona pandemic. The search for new modes of teaching-learning and training began during the lockdown. In current society, Digital Social Media Networking Technologies (DSMNT) are powerful pedagogical resources; however, they require special teacher training. Using DSMNT to support educational endeavours leverages the benefits of in-person learning groups or communities, along with the benefits of using technology to support student system involvement. The research study begins with a reflection of the use of training teachers in the utilisation of DSMNT and the curriculum, or the pedagogical use of DSMNT. The research paper closes with a discussion of the benefits and challenges of DSMNT (Social Networking) based on the data obtained from questionnaires, observations and posts of students/others on the network. Despite the difficulties, the use of DSMNT was recognised as positive during COVID-19.